Fasting plasma insulin concentrations are associated with changes in hepatic fatty acid synthesis and partitioning prior to changes in liver fat content in healthy adults - Hodson, L; Karpe, F; Pavlides, M; Banerjee, R; McNeil, C; Neubauer, S (American Diabetes Association, 2016)
Resistance to the action of insulin impacts on fatty acid delivery to the liver, fatty acid synthesis and oxidation within the liver and triglyceride export from the liver. To understand the metabolic consequences of hepatic fatty acid synthesis, partitioning, oxidation and net liver fat content in the fasted and postprandial states we studied healthy men and women with varying degrees of insulin resistance before and after consumption of a mixed meal using stable-isotope tracer methodologies. Subjects were classified as being either normoinsulinemic (NI) (fasting plasma insulin <11.2 mU/L), n=18 or hyperinsulinemic (HI) (fasting plasma insulin >11.2 mU/L, n=19). There was no difference in liver fat content between HI and NI individuals, despite HI subjects having marginally more visceral fat. However, compared with NI subjects de novo lipogenesis (DNL) was higher and fatty acid oxidation was lower in HI individuals. These data suggest that metabolic pathways promoting fat accumulation are enhanced in HI but paradoxically without any significant impact on liver fat content when observed in healthy people. This is likely to be explained by increased triglyceride secretion as observed by hypertriglycerideaemia.